Social Support and Community Practices in Poverty Alleviation: A Study of ‘Kampung Idiot’ Ponorogo - Ferina Choirunnisa (Pusat Riset dan Inovasi Nasional, 2025)
Poverty is a complex social issue, particularly in underdeveloped areas like Karangpatihan Village, which is known as the